2021
DOI: 10.1186/s13071-021-05091-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of two clip domain serine proteases in innate immune responses of Aedes aegypti

Abstract: Background Clip domain serine proteases (CLIPs), a very diverse group of proteolytic enzymes, play a crucial role in the innate immunity of insects. Innate immune responses are the first line of defense in mosquitoes against the invasion of pathogenic microorganisms. The Toll pathway, immunodeficiency (IMD) pathway and melanization are the main processes of innate immunity in Aedes aegypti. CLIPS are classified into five subfamilies—CLIPA, CLIPB, CLIPC, CLIPD, and CLIPE—based on their sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Furthermore, our data uncovers polymorphisms in genes of the CLIP B and D like serine protease subfamilies, corroborating earlier RNAseq reports [61]. Notably, CLIP-B is the major sub-family, members like CLIPB15, CLIPB9, and CLIPA14, alongside CLIPB8, participate in prophenoloxidase activation in melanisation process and play roles in the Toll and IMD pathways of the innate immune response in Aedes mosquitoes [76,77]. Our results align with previous study [35], where Dengue virus and Rift valley fever virus infected Ae.…”
Section: Sequence Variation In Genes Encoding Serine Proteases and Th...supporting
confidence: 90%
“…Furthermore, our data uncovers polymorphisms in genes of the CLIP B and D like serine protease subfamilies, corroborating earlier RNAseq reports [61]. Notably, CLIP-B is the major sub-family, members like CLIPB15, CLIPB9, and CLIPA14, alongside CLIPB8, participate in prophenoloxidase activation in melanisation process and play roles in the Toll and IMD pathways of the innate immune response in Aedes mosquitoes [76,77]. Our results align with previous study [35], where Dengue virus and Rift valley fever virus infected Ae.…”
Section: Sequence Variation In Genes Encoding Serine Proteases and Th...supporting
confidence: 90%
“…Notable enrichment of CLIP-domain serine protease and serine protease inhibitor genes was observed under the ontology category of serine-type endopeptidase activity ( Figure 6B ; Figure S6B) . Although the function of serine protease and serine protease inhibitors in mosquitoes have mostly been studied with respect to their role in innate immune response ( 55 , 56 ), their physiological relevance is underexplored. It has become increasingly evident that these groups of proteins are widely expressed in brain cells and have a long-term impact on the plasticity, memory, cognition, and behavior of the organism ( 39 , 45 , 57 ).…”
Section: Resultsmentioning
confidence: 99%
“…berghei ookinete melanization [ 50 52 ]. Wang et al (2021) have reported that silencing of CLIPB15 leads to a significant decrease in Phenoloxidase (PO) activity, which acts as a catalyst for the formation of active intermediates of quinone for the synthesis of melanin, but silencing of CLIPB22 does not alter the PO activity [ 48 ]. Silencing of both CLIPB15 and CLIPB22 affects the survival of Ae .…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of both CLIPB15 and CLIPB22 affects the survival of Ae . aegypti after pathogenic bacterial infection [ 48 ]. Consistent with these studies, we identified three CLIP domain-containing serine proteases, two of which, CLIPB2 and CLIPB4 , were primarily upregulated in Wolbachia -infected blood-fed An .…”
Section: Discussionmentioning
confidence: 99%